Change Management: Dampak Perubahan Dengan Adanya Implementasi IT - Widjaya, Iwan Kurniawan (Bina Nusantara University, 2010)
Technology improvement has brought much changes in how businesses and organizations have to run properly in global competitions. But the most important thing is the changing in organizations and people who will operate with the integrations systems. Resistance always happens in every implementations and it will be the main problems in every company. In this paper, it will be explored more in details about the cause and effect from the changes that will happens before and after the implementations, including how to utilize the result of the implementations in order to get the benefits for the business. Another important things are including the strategy and planning of changes that should be effectively implemented and given the maximum contributions to support the future development and synergy with business planning. This paper is also given the guidance about how to act and do some preventive actions in managing better ways in setting up the planning of changes in implementations of Information Technology and systems in the best ways.